Reproductive morphology of the early-divergent grass Streptochaeta and its bearing on the homologies of the grass spikelet - Sajo, M. G. [UNESP]; Longhi-Wagner, H. M.; Rudall, P. J. (Springer Wien, 2008)
Reproductive morphology and development are described in the Brazilian grass Streptochaeta spicata, in order to assess the homologies of the characteristic grass inflorescence, termed a spikelet, and other reproductive organs. Streptochaeta possesses some features that are commonly found in Poaceae, including a well-differentiated embryo. It also possesses some relatively unusual, presumably derived features, such as non-plumose stigmas, which indicate that it could be insect-pollinated. It shares some features with other early-divergent grasses, such as Pharus, which could represent plesiomorphic conditions for grasses. The inflorescence unit in Streptochaeta has been interpreted as a compound branching system or pseudospikelet. The present data suggest that it is a highly modified spikelet, with a modified flower borne either on a different axis to the basal bracts (glumes) or on the same axis as the basal bracts. The three bracts below the stamens are interpreted as homologous to the lodicules. The Streptochaeta spikelet could be considered as morphologically intermediate between the true spikelet of grasses and reproductive units of close grass relatives.
Keywords: Caryopsis; Grass flower; Grass spikelet; Inflorescence; Scutellum